Intra action review of the cholera outbreak response in Kadoma city, Zimbabwe, 2024 - Clayton Munemo; Chido Zibanayi; Hamilton Gomba; Precious Banda; Sarah Tengawarima; Sikhanyisiwe Moyo; Daniel Chirundu (BMC Public Health)
Abstract Background An Intra-Action Review (IAR) is a real-time evaluation conducted during an emergency response to identify good practices, challenges and inform corrective actions. It allows for timely learning and course correction during ongoing outbreaks. In 2024, Kadoma City experienced a cholera outbreak that resulted in 1799 cases managed at the Cholera Treatment Center (CTC), 2535 suspected cases seen at Oral Rehydration Points (ORPs), and 31 deaths. As part of the response, an IAR was conducted, led by Kadoma City Council, to evaluate coordination, identify challenges, and document best practices to improve the current response and strengthen preparedness for future outbreaks. Methods The IAR employed a qualitative and participatory approach following WHO methodology to assess cholera outbreak response activities in Kadoma City. The IAR reviewed response activities from January 4 to April 30, 2024, and was conducted in-person on May 2, 2024, using a working group format. The working groups covered eight response pillars aligned to the five core functions of the Incident Management System (IMS). Out of 83 participants invited, 77 (92.8%) attended and these included representatives from Kadoma City Council, Ministry of Health and Child Care (MoHCC) and partner organizations such as Africa Center for Disease Control and Prevention (Africa CDC), WHO and Médecins Sans Frontières (MSF). Data were collected using standardized IAR note-taking templates covering all eight response pillars and analyzed thematically to identify best practices, challenges, and recommendations. Results The IAR was attended by seventy-seven (77) participants. Several best practices that enhanced the cholera outbreak response were identified. These included the use of the IMS to provide structured coordination, marking the first activation of all five core IMS functions for a cholera outbreak response in Kadoma. Daily analysis of surveillance data which supported informed decision-making. The use of community health workers (CHWs) in community event-based surveillance (CEBS), enabling early case detection. Additionally, incorporating cholera survivors into risk communication and community engagement (RCCE) activities improved public awareness and increased acceptability of outbreak interventions. Key challenges noted included the absence of a dedicated physical Public Health Emergency Operations Center (PHEOC); transport constraints affecting movement of supplies, patients, and surveillance teams; human resource fatigue; shortages of infection prevention and control (IPC) resources and limited laboratory surveillance capacity due to shortages of rapid diagnostic test kits and inadequate capability to conduct culture-based identification of microorganisms. Also, inadequate consideration of people with disabilities in RCCE strategies was noted. Conclusion The structured response approach in Kadoma improved coordination, data use, and community-level case detection. However, challenges such as absence of a PHEOC, transport constrains, limited laboratory capacity, and supplies highlighted the need for stronger emergency preparedness and inclusive response systems.